CONSTRUCTING “NEW FATHERHOOD” IN DIGITAL PRACTICE: ON LINE SELF-PRESENTATION OF DAD BLOGGERS ON CHINA SELF-MEDIA PLATFORMS - Wang Li; Fairuz A’dilah Rusdi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
As society changes, the role of fathers in China is also evolving, and the emergence of “new fathers” has prompted scholars to pay more attention to the importance of father involvement in China. This study selected six father bloggers from Little red book (a social networking site, the most popular social media in China today) as the subjects of the study and adopted the theoretical framework of fatherhood proposed by Casey Scheibling, i.e., the experience of fatherhood, identity, and ideology of fatherhood, as well as the qualitative analysis method to specifically analyze their fatherhood experiences. Using qualitative analysis methods, the parenting routines of six blogger dads were specifically analyzed. The data analysis showed that dad bloggers are shaping a new fatherhood by identifying with caring fatherhood, focusing on building harmonious and intimate relationships, concentrating on scientific parenting, and alleviating maternal parenting anxieties. Modern fathers can learn from these new concepts and practices: shifting from “authoritative discipline” to “emotional accompaniment” and practicing caring fatherhood. Fathers’ participation in parenting is not a “favor” but a shared responsibility. Emphasis is placed on the management of the couple’s relationship in order to enhance the level of parenting involvement. The findings of this study will serve as a reference for building a more complete and healthy family parenting ecosystem.